Evolution favours aging in populations with assortative mating and in sexually dimorphic populations - Lenart, Peter; Bienertová-Vašků, Julie; Berec, Luděk (Scientific reports, 2018)
Since aging seems omnipresent, many authors regard it as an inevitable consequence of the laws of physics. However, recent research has conclusively shown that some organisms do not age, or at least do not age on a scale comparable with other aging organisms. This begets the question why aging evolved in some organisms yet not in others. Here we present a simulation model of competition between aging and non-aging individuals in a sexually reproducing population. We find that the aging individuals may outcompete the non-aging ones if they have a sufficiently but not excessively higher initial fecundity or if individuals mate assortatively with respect to their own phenotype. Furthermore, the aging phenotype outcompetes the non-aging one or resists dominance of the latter for a longer period in populations composed of genuine males and females compared to populations of simultaneous hermaphrodites. Finally, whereas sterilizing parasites promote non-aging, the effect of mortality-enhancing parasites is to enable longer persistence of the aging phenotype relative to when parasites are absent. Since the aging individuals replace the non-aging ones in diverse scenarios commonly found in nature, our study provides important insights into why aging has evolved in most, but not all organisms.
Keywords: Animals; rozmnožování; Female; Phenotype; teoretické modely; biologická evoluce; ženské pohlaví; Reproduction; Aging; fertilita; sexuální výběr u zvířat; Sex Characteristics; Mating Preference, Animal; Genetics, Population; Fertility; Male; pohlavní dimorfismus; stárnutí; fenotyp; zvířata; mužské pohlaví; Biological Evolution; Models, Theoretical; populační genetika